Becoming Sincere: Why Do Jewish Inmates in Israeli Prisons Embrace Religion? - Morag, Michal (International journal of offender therapy and comparative criminology, 2021)
Why do Jewish inmates in Israeli prisons embrace religion? What initially motivates them to participate in prayers during incarceration and what are their motivations to make a deeper commitment to observe orthodox Judaism while in prison? We conducted 30 qualitative interviews with 29 Jewish–Israeli men who underwent a process of “religious invigoration” or “religious strengthening” during their prison term and chose to continue being observant following release. We examine their motivations to initially participate in the less restrictive prison seminaries as well as their motivations to transfer to religious wards where incarcerated men must commit to a fully religious lifestyle. Building on the scholarship on the motivations and benefits of religious participation and conversion in prison, we suggest that incarcerated Jewish–Israeli men embrace religion for both sincere reasons and for the extrinsic benefits. Those who progress to a second stage of religious observance and transfer to religious wards do so primarily for extrinsic benefits. However, they report many intrinsic benefits of religion that lead them to continue to pursue religion once released. We suggest that men have different motivations at different stages of the path of religious invigoration in prison but that those men who commit to observance gain intrinsic benefits that may give them sincere reasons to continue religion upon reentry.